Rancangan Tata Letak Fasilitas Ruang Produksi Roti Tawar Daun Katuk Skala Mini Pabrik - Tirza M Avianti; Murdani Murdani; Titik Budiati (JOFE : Journal of Food Engineering, 2022)
The design of the layout of the production room aims to support the smooth production process, make the movement of labor more efficient and raw materials that are not needed, determine the coordination of each production room which is arranged in such a way as to be able to support the maximum effectiveness and efficiency of production operations, as well as to prevent work accidents. The research method used is a field study which includes observations and interviews. Literature study was conducted by referring to previous research relevant to the problem. The results obtained are a map of the operation process to control the production process, the factory capacity per day is 80 units of white bread, per month of 1,600 units of white bread and 19,200 per year, the number of tools and machines needed is 49, 27 operators, and 18 production rooms with The total area of the factory required is 590.28 m2.